Aloe emodin induces apoptosis in ER+-breast cancer cells; MCF-7 through IGF-1R signalling pathway - Indah Mohd Amin,; Roziana Kamaludin,; Swee, Keong Yeap; Mohamad Rodi Isa,; Nik Mohd Mazuan Nik Mohd Rosdy,; Rosfaiizah Siran,; Siti Hamimah Sheikh Abdul Kadir,; Narimah Abdul Hamid Hasani, (Universiti Kebangsaan Malaysia, 2015)
Two-third of breast cancer patients expressed estrogen receptors (ER)s and received endocrine treatment with established anti-estrogens such as tamoxifen. But the action and acquired resistance during treatment are largely unknown. In contrary, phytochemicals are more selective and less cytotoxic to normal cells. Accordingly, we found aloe emodin, an anthraquinone to inhibit the proliferation of ER+-breast cancer cells, MCF-7 with IC50 of 80 μM, but not affecting control breast cells, MCF-10A. Tamoxifen was non-selective to both cells with IC50 of 27 and 38 μM, respectively. Thus, we aimed to investigate the anti-proliferative mechanism of aloe emodin on MCF-7 and its underlying signalling compared to tamoxifen. Cells were treated separately with aloe emodin and tamoxifen at respective IC50 for 72 h. Apoptosis was determined using Annexin V-FITC/PI staining. The expression of insulin-like growth factor-1 receptor (IGF-1R), insulin-like growth factor binding protein (IGFBP)-2 and B-raf gene was investigated using QuantiGene 2.0 Plex assay. Paired-student t-test and ANOVA test were used to compare between untreated and treated cells on the measured parameters. Each treatment was conducted in triplicate and repeated three times. Significance was set at p<0.05. The presences of early and late apoptosis in MCF-7 were seen in both treatments. All target genes were down regulated. The anti-proliferation effect of aloe emodin on MCF-7 is similar with tamoxifen which mediates inhibition of IGF-1R signalling pathway. This suggests aloe emodin as a potential anti-cancer agent to be used in combined anti-estrogen therapy to enhance its efficacy in ER+-breast cancer treatment.